Personal Communication in Digital Learning: Unveiling Its Impact on Engagement and Knowledge Dynamics - Zakia Jamali (Journal of Aceh Studies, 2025)
Background of the problem: This systematic literature review examines the changing significance of human contact in digital learning environments since the 1990s, highlighting a significant gap in comprehending its precise influence on learning dynamics. Purpose: The study sought to investigate the fundamental motives thoroughly for personal sharing, the specific importance of feedback, the expression and modification of current communication theories, and the observable impacts on both online and organizational learning outcomes. Method: A descriptive, qualitative systematic literature review was conducted, with data meticulously collected from prominent scientific databases such as Scopus and Web of Science and processed through thematic synthesis. Result: Essential studies indicate that incentives for personal communication include the intrinsic human desire for connection, cognitive involvement for collaborative knowledge creation, and emotional expression for support. Feedback is recognized as a crucial component, defined by its promptness, customization, and reciprocal nature. Littlejohn's communication theory exhibits persistent relevance, adjusting to an increased array of digital symbols and dynamic online environments. Personal communicative acts greatly improve student engagement, satisfaction, and academic success in online education, while also promoting knowledge exchange, innovation, and adaptability within corporate learning frameworks. Implication: These findings show that it's important to build online learning spaces that focus on real personal connections and strong feedback, which can improve how effective and engaging education and organizational growth can be.